Estudios y Diseños para la pavimentacion y Drenaje Pluvial de la Calles de la Ciudadela: los Ceibos y San José, de la ciudad de Arenillas, Provincia de el Oro, Año 2014 - Quitio Quitio, Samuel Orlando (2015)
The streets of the citadels: The Ceibo and San Jose City Grit is in poor condition, making it difficult Vehicular and pedestrian mobility, also cause health problems due to dust that rises when transiting vehicles, another drawback is the sludge that forms when it rains. All of these problems limit the development of the sector, for this reason, this work degree aims to make the geometric design, structural and rainwater drainage from the streets.